2008
DOI: 10.1590/s0100-879x2008005000050
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear calcium signaling: a cell within a cell

Abstract: Calcium (Ca 2+ ) is a versatile second messenger that regulates a wide range of cellular functions. Although it is not established how a single second messenger coordinates diverse effects within a cell, there is increasing evidence that the spatial patterns of Ca 2+ signals may determine their specificity. Ca 2+ signaling patterns can vary in different regions of the cell and Ca 2+ signals in nuclear and cytoplasmic compartments have been reported to occur independently. No general paradigm has been establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…Ca 2+ signals within the nucleus are particularly important in cancer cell progression [50, 59, 60]. Buffering nuclear Ca 2+ arrests adenocarcinoma cells in the early phase of mitosis [61], and sensitizes head and neck cancer cells to radiotherapy [59].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ signals within the nucleus are particularly important in cancer cell progression [50, 59, 60]. Buffering nuclear Ca 2+ arrests adenocarcinoma cells in the early phase of mitosis [61], and sensitizes head and neck cancer cells to radiotherapy [59].…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that the cell nucleus contains the whole set of enzymes required for the InsR 3 synthesis from diphosphoinositolphosphate of the nuclear membrane, so the regulation of nuclear InsP 3 Rs cannot depend on cytoplasmic processes (Gomes et al, 2006; Klein and Malviya, 2008; Rodrigues et al, 2009). Of course, in small cells InsR 3 can freely penetrate into the nucleus by diffusion through the nuclear pores, but in large cells the distance from the plasma membrane to the nucleus is large enough so it is unlikely that InsP 3 Rs in the nuclear membrane are activated by cytosolic InsP 3 R. This point is proved by the fact that that numerous InsP 3 -activated channels were recorded from the inner nuclear membrane of Purkinje and CA1 pyramidal neurons, which are the largest cells in the brain.…”
Section: Insp3rs In Cell Functionsmentioning
confidence: 99%
“…Thus, glutamate uptake at the synapse is proposed to give rise to Ca 2þ release from the nuclear lumen directly into the nucleus (O'Malley et al 2003;Jong et al 2005Jong et al , 2007Sheldon and Robinson 2007;Kumar et al 2008). This model is bolstered by data documenting the presence and functional responsiveness of EAATs, mGluRs, and IP 3 Rs on the inner nuclear membranes of a variety of cell types including dissociated neurons (Humbert et al 1996;Echevarria et al 2003;Gerasimenko et al 2003;O'Malley et al 2003;Jong et al 2005Jong et al , 2007Marchenko et al 2005;Quesada and Verdugo 2005;Marchenko and Thomas 2006;Sheldon and Robinson 2007;Kumar et al 2008;Bootman et al 2009;Rodrigues et al 2009). It remains to be seen, however, whether and under which conditions internal Ca 2þ release mediated by intranuclear mGluRs and IP 3 Rs can be evoked in intact brain tissue.…”
Section: Generating Nuclear Ca 2þ Signalsmentioning
confidence: 99%